Rotavirus VP6 protein expressed in cell culture by HSV-1-based vectors - Palacios, Carlos Adolfo (2015)
HSV-1 vectors were developed for the expression of several rotavirus genes. Genes from other pathogens were also expressed, thus generating a set of tools to be tested as new vaccine candidates against In this section, we show two different HSV-1 vectors that express the VP6 protein from different rotavirus strains. Figure 1 shows a defective recombinant virus expressing simultaneously EGFP and VP6 from murine rotavirus strain EC, In Figure 2, an amplicon vector overexpressing VP6 from a Wa strain of human Rotavirus is shown. In both cases, the VP6 proteins were recognized by a monoclonal antibody and were found extensively expressed forming filaments along the cells, showing a typical intra-cellular pattern, in the absence of other rotavirus proteins. These results show that the recombinant proteins maintain the specific capacity of self-assembly of the native protein and, therefore, are potential vaccine candidates to be explored.